Brand advocacy : a scoping review and future research agenda - Shimul, Anwar Sadat; Faroque, Anisur R.; Quader, Esnaina (Emerald, 2025)
Purpose The purpose of this paper is to conduct a comprehensive scoping review to examine how brand advocacy has evolved as a key construct in consumer–brand relationship research. Through systematic analysis of existing literature, this review clarifies the conceptual boundaries of brand advocacy, synthesises current knowledge and develops an agenda for future research. Design/methodology/approach By reviewing a selection of 172 studies, this research explores various aspects of the brand advocacy literature, including theories, methods, contexts, antecedents, outcomes, mediators and moderators. The review examines key themes and synthesises the theoretical and contextual foundations. Findings This review identifies significant gaps in the current literature, particularly regarding conceptual clarity and consistency, framework development, validation and contextual measurements. The findings of this study suggest guidelines for future research to advance scholarly understanding of brand advocacy. Research limitations/implications The insights from this review offer guidance for researchers and practitioners looking to advance the field of brand advocacy. This study highlights the importance of creating validated frameworks and addressing measurement issues to integrate the brand advocacy concept into consumer–brand relationship research. Originality/value This scoping review advances the field of brand advocacy by synthesising existing research, identifying critical gaps and proposing a coherent research agenda for future studies. This study contributes to the broader understanding of consumer–brand relationships and provides a foundation for developing more robust theoretical and practical frameworks in the domain.
Keywords: Brand advocacy; Scoping review; Consumer-brand relationship; Brand identification; Relationship marketing; fi=Kansainvälinen liiketoiminta|en=International Business|